Metodologia de desenvolvimento e validação de kit imunocromatográfico adotando como modelo o teste rápido para detecção do hormônio luteinizante (LH) - Camargo, Maria Angélica de (Universidade Federal de São Carlos, 2015)
Despite the rapid tests market in Brazil being in full expansion, the country does not have a tradition of manufacturing these kits. Therefore, it is very difficult to find, in the national literature, reports to guide the development process of these kits. The lack of published reports is aggravated by the difficulty of understanding the rules and laws governing the sector and by their subjectivity. The aim of this study was to describe a methodology to develop and validate a diagnostic kit, according to prevailing regulations. For this, a self-diagnostic semiquantitative kit for detection of Luteinizing Hormone (LH), using the rapid test platform, was taken as a model and all the procedures required in each stage of the design of the product, including planning, development and validation, have been described. The kit developed complied with all established operating requirements and achieved 97.39% sensitivity and 97.92% specificity. The cross-reaction tests showed that the kit suffers interference from samples containing hCG, due to the high similarity of beta chains of the hormones. Despite this fact, the performance of the test was better than the performance of the kit available in the market today. Based on the results obtained, we conclude that the procedures presented, which comply with the management standards ISO 9001:2008 and ISO 13485:2004 and also with the Good Manufacturing Practices of the RDC 16/2013, were effective in obtaining the kit and may be used as a model for management and development of similar projects within companies operating in the diagnostic market.
Keywords: Imunologia; Hormônio luteinizante; Teste rápido; Metodologia; Desenvolvimento de produtos; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS